Dakwah Pada Masyarakat Daerah Terpencil: Metode Da’wah bi al-Hal Sebagai Upaya Meningkatkan Taraf Kehidupan Mad’u - Muhammad Ahnu Idris (LP2M IAI Miftahul Ulum Pamekasan, 2018)
This article discusses methods of da'wah bi al-things in order to improve the lives of people in remote areas. Qualitative analysis, with the results of this paper was elaborated in the form of discussion based on literature and existing data. This topic is based on the assumption of reality in a society that assumes that the Da'wah only as a religious lecture, and lack of attention by activist preaching about the importance of this method to change the condition of a remote community have a low level of education, economic level intermediate down, less master SCIENCE and TECHNOLOGY. These themes became important, as the progress and setbacks of Islamic Da'wah activities largely determined by which become the duty of every muslim.